A facile and efficient strategy for the fabrication of porous linseed gum/cellulose superabsorbent hydrogels for water conservation. (10th February 2017) - Zhang, Hao; Luan, Qian; Huang, Qingde; Tang, Hu; Huang, Fenghong; Li, Wenlin; Wan, Chuyun; Liu, Changsheng; Xu, Jiqu; Guo, Pingmei; Zhou, Qi
Highlights: A simple method is presented to develop linseed gum/cellulose hydrogels. Linseed gum/cellulose hydrogels have interpenetrating porous structure. Linseed gum/cellulose hydrogels possess superabsorbent property. Water retention property allows the hydrogel to be used in water-saving. Abstract: The linseed gum/cellulose composite hydrogels were successfully fabricated by mixing cellulose and linseed gum solutions dissolved in the NaOH/urea aqueous system and cross-linked with epichlorohydrin. The morphology and structure of the composite hydrogels were investigated by scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, X-ray diffractometry (XRD) and thermogravimetric analysis (TGA). The swelling ratio and water retention properties were investigated. The results revealed that linseed gum mainly contributed to water adsorption, whereas the cellulose acted as a backbone to strengthen the porous structure. This work provided a simple way to prepare cellulose-based superabsorbent hydrogels, which could be potentially applied as an effective water conservation material in agriculture.